Iron-catalyzed indolizine synthesis from pyridines, diazo compounds, and alkynes - Douglas, Tim; Pordea, Anca; Dowden, James (American Chemical Society, 2017)
The iron (III) catalyzed synthesis of indolizines from commercially available alkyne, pyridine, and diazo precursors is reported. This mild, expedient method is tolerant of various solvents and proceeds with as little as 0.25 mol % [Fe(TPP)Cl]. Significantly, this multicomponent reaction is compatible with electrophilic alkynes; control experiments demonstrate the importance of the catalyst in promoting pyridinium ylide formation over background reactivity.